MYC high level gene amplification is a distinctive feature of angiosarcomas after irradiation or chronic lymphedema - Manner, Johanna M.; Radlwimmer, Bernhard; Hohenberger, Peter; Mößinger, Katharina; Küffer, Stefan; Sauer, Christian; Belharazem, Djeda; Zettl, Andreas; Coindre, Jean-Michel; Hallermann, Christian; Hartmann, Jörg Thomas; Katenkamp, Detlef; et al. (The American journal of pathology, 2010)
Angiosarcomas (AS) are rare vascular malignancies that arise either de novo as primary tumors or secondary to irradiation or chronic lymphedema. The cytogenetics of angiosarcomas are poorly characterized. We applied array-comparative genomic hybridization as a screening method to identify recurrent alterations in 22 cases. Recurrent genetic alterations were identified only in secondary but not in primary AS. The most frequent recurrent alterations were high level amplifications on chromosome 8q24.21 (50%), followed by 10p12.33 (33%) and 5q35.3 (11%). Fluorescence in situ hybridization analysis in 28 primary and 33 secondary angiosarcomas (31 tumors secondary to irradiation, 2 tumors secondary to chronic lymphedema) confirmed high level amplification of MYC on chromosome 8q24.21 as a recurrent genetic alteration found exclusively in 55% of AS secondary to irradiation or chronic lymphedema, but not in primary AS. Amplification of MYC did not predispose to high grade morphology or increased cell turnover. In conclusion, despite their identical morphology, secondary AS are genetically different from primary AS and are characterized by a high frequency of high level amplifications of MYC. This finding may have implications both for the diagnosis and treatment of these tumors.
Gesehen am 04.05.2023